2021
DOI: 10.3390/w13243608
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Removal Performance of Denitrifying Woodchip Bioreactors in Tropical Climates

Abstract: In Australia, declining water quality in the Great Barrier Reef (GBR) is a threat to its marine ecosystems and nitrate (NO3−) from sugar cane-dominated agricultural areas in the coastal catchments of North Queensland is a key pollutant of concern. Woodchip bioreactors have been identified as a potential low-cost remediation technology to reduce the NO3− runoff from sugar cane farms. This study aimed to trial different designs of bioreactors (denitrification walls and beds) to quantify their NO3− removal perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…Genes for full-fledged denitrification were detected in seven MAGs where five of them also had genes for DNRA. 4, Figure S4), while none for DNRA, suggesting that denitrification is the dominant NO 3 reducing pathway in our data, as also indicated in previous WBR studies 9,11,[51][52][53] . Expressed enzymes included napAB (one enzyme), narGHI (14 enzymes), nirK (one enzyme), nirS (12 enzymes), norBC (six enzymes), nosZ (10 enzymes).…”
Section: A Microbiome Enriched For Lignocellulose-degrading Denitrifierssupporting
confidence: 87%
“…Genes for full-fledged denitrification were detected in seven MAGs where five of them also had genes for DNRA. 4, Figure S4), while none for DNRA, suggesting that denitrification is the dominant NO 3 reducing pathway in our data, as also indicated in previous WBR studies 9,11,[51][52][53] . Expressed enzymes included napAB (one enzyme), narGHI (14 enzymes), nirK (one enzyme), nirS (12 enzymes), norBC (six enzymes), nosZ (10 enzymes).…”
Section: A Microbiome Enriched For Lignocellulose-degrading Denitrifierssupporting
confidence: 87%
“…It is also possible that the increase in ammonium concentrations could be due to inputs from groundwater seeps and/ or ammonification of DON. Past studies found elevated ammonium concentrations in outflow from denitrifying bioreactors, which was attributed to mineralization of DON from decay of carbonaceous material (Fenton et al 2016;Pfannerstill et al 2016;Manca et al 2021). Most studies on IBRs reported similar ammonium concentrations between inflow and outflow (Robertson and Merkley 2009;Elgood et al 2010;Maxwell et al 2022;Burb-ery and Abraham 2022) suggesting that DNRA and biodegradation was minimal.…”
Section: Nitrogen Transformation and Controlling Factorsmentioning
confidence: 97%